An Autosomal Translocation 73,XY,t(12;20)(q11;q11) in an Infertile Male Llama (Lama glama) With Teratozoospermia - Baily, Malorie P.; Avila, Felipe; Das, Pranab J.; Kutzler, Michelle A.; Raudsepp, Terje (Frontiers in Genetics, 2019)
Structural chromosome abnormalities, such as translocations and inversions occasionally occur in all livestock species and are typically associated with reproductive and developmental disorders. Curiously, only a few structural chromosome aberrations have been reported in camelids, and most involved sex chromosomes. This can be attributed to a high diploid number (2n=74) and complex chromosome morphology, which makes unambiguous identification of camelid chromosomes difficult. Additionally, molecular tools for camelid cytogenetics are sparse and have become available only recently. Here we present a case report about a sterile male llama with teratozoospermia and abnormal chromosome number 2n=73,XY. This llama carries an autosomal translocation of chromosomes 12 and 20, which is the likely cause of defective spermatogenesis and infertility in this individual. Our analysis underlines the power of molecular cytogenetics methods over conventional banding-based chromosome analysis for explicit identification of normal and aberrant chromosomes in camelid karyotypes. This is the first case of a translocation and the first autosomal aberration reported in any camelid species. It is proof of principle that, like in other mammalian species, structural chromosome abnormalities contribute to reproductive disorders in camelids.